Examining the association between hooking up and marital processes and quality - Johnson, Matthew David (Kansas State University, 2012)
The current study tests a theoretical model exploring the relationship between hooking up and marital quality and whether this relationship is mediated by sexual satisfaction and communication using public-use data from currently married participants in Wave IV of the National Longitudinal Study of Adolescent Health (Add Health, n = 1,729). Gender proved to significantly moderate the association between the variables in the model, but college education did not. The results indicate that hooking up has a direct negative relationship with marital quality for men that is not mediated by either sexual satisfaction or communication. The results for women revealed no direct relationship between hooking up and marital quality, but an indirect influence via communication.
Keywords: Hooking up; Marriage; Structural equation modeling; Sexuality; Social Research (0344)